Exposing The Criteria For Fake Hadith In The Science Of Mustolahul Hadith - Nasiri (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2024)
Scholars differ on when the forgery of hadith began. People have falsified various hadiths for varying motives and purposes. Furthermore, for certain interests, people are able and willing to fabricate them. The term "hadith" is defined as a hadith attributed to the Prophet Muhammad (peace be upon him) fabricated and false, even though he did not actually say he did or established it. Using a "mawdu'" hadith is invalid, and it is forbidden to narrate it unless forced or to have the hadith examined by a scholar. Based on existing historical data, hadith forgery is not only carried out by Muslims but also by non-Muslims for various motives and interests, including political conflict, the efforts of heretics, fanaticism towards nations and tribes, influencing the laity, and so on.